Measuring Technological Forecasting - (:unkn) unknown (IEEE, 2009)
The importance of technological forecasting is increasing due to immense effect of technology on the organizations. Accurate forecast will obviously yield more benefit in shorter time scales. Although there are so many studies to forecast the single technological aspect of certain products, such as Flight Speed or Bomber Carriage of air fighters, a general model to forecast overall technological changes is yet to be developed. In this paper, a methodology of measuring the capability of forecasting the technological changes with respect to Throughput Time, Quantity per Day, Rework Rate, and New Investment Revenue is presented.